25. KERJASAMA BADAN NARKOTIKA NASIONAL DENGAN UNITED NATIONS OFFICE ON DRUG AND CRIME DALAM MENANGGULANGI PERDAGANGAN GELAP NARKOBA DARI IRAN KE INDONESIA 2009-2013 - Dyartha Anindya Nugraheni; Tri Cahyo Utomo; Shary Charlotte Pattipelohy (Journal of International Relations Diponegoro, 2016)
Illicit drug trafficking is an example of Transnational Organized Crime. The location,geographical conditions and high demand of illegal drugs have made Indonesia highlyvulnerable towards a member of drug crime activities. Iran is the second largest country thatsmuggles drugs of Shabu to Indonesia. In tackling illicit drug trafficking from Iran toIndonesia, the National Narcotics Board (BNN) initiating cooperation with United NationsOffice on Drug and Crime (UNODC). Descriptive Analytic approach is used to explain theform and result of BNN and UNODC cooperation. The result of this research shows that eventhough supports have been given to BNN, the issue has not been succesfully tackled. UNODCand BNN need to improve efforts in combating illicit drug trafficking to keep Indonesiasecured and prosper.